2010
DOI: 10.3109/07420528.2010.501927
|View full text |Cite
|
Sign up to set email alerts
|

DIURNAL, AGE, AND IMMUNE REGULATION OF INTERLEUKIN-1β AND INTERLEUKIN-1 TYPE 1 RECEPTOR IN THE MOUSE SUPRACHIASMATIC NUCLEUS

Abstract: Circadian clocks serve to impose a near-24-h temporal architecture on an organism's physiology, metabolism, and behavior. In mammals, the suprachiasmatic nucleus (SCN) of the hypothalamus functions as the master circadian pacemaker. There is growing evidence that immunomodulators, such as cytokines, may impinge on circadian timekeeping. We examined whether there is endogenous expression of the proinflammatory cytokine interleukin-1β (IL-1β) and its signaling receptor IL-1R1 in the SCN of young and older mice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 48 publications
2
43
1
Order By: Relevance
“…For example, cFOS was increased in the reward circuitry following HFD [120] and in the dorsomedial and lateral hypothalamus [121]. cFOS is similarly induced following LPS treatment in the hypothalamus [122] and this induction is location specific [123]. These studies also postulated that the location is dependent on the neuron function and suggested that cFOS was induced following neuron activation, since cFOS is the most commonly used marker of neuronal activity.…”
Section: Discussionmentioning
confidence: 92%
“…For example, cFOS was increased in the reward circuitry following HFD [120] and in the dorsomedial and lateral hypothalamus [121]. cFOS is similarly induced following LPS treatment in the hypothalamus [122] and this induction is location specific [123]. These studies also postulated that the location is dependent on the neuron function and suggested that cFOS was induced following neuron activation, since cFOS is the most commonly used marker of neuronal activity.…”
Section: Discussionmentioning
confidence: 92%
“…One aspect that might be of importance is the role of neuroinflammation in AD on SCN and circadian function. Alzheimer's disease, like many other neurodegenerative diseases, is associated with neuroinflammation (91) which can impact on SCN and circadian function (9,92,93). Another area worthy of further investigation is the role that cholinergic cell loss has in circadian rhythm disturbance in AD and whether anti-cholinesterase drugs might impact on such rhythms in AD.…”
Section: Discussionmentioning
confidence: 99%
“…The timekeeping apparatus of the SCN is a molecular mechanism that involves both transcriptional repressor genes, as well as transcriptional activators, which together create a feedback loop generating circadian oscillations (17). Cytokines such as IL-1 and TNF downregulate the expression of some of these clock genes (6,11). Signaling receptors for IL-1 and TNF are distributed throughout the brain, including the hypothalamus (2, 5), and IL-1 signaling receptors are present in the SCN (6).…”
Section: Discussionmentioning
confidence: 99%